2019
DOI: 10.1111/cas.13975
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of intrapancreatic neural density in cancer tissue predicts poorer outcome in pancreatic ductal carcinoma

Abstract: Neural invasion is one of the malignant features contributing to locally advanced and/or metastatic disease progression in patients with pancreatic ductal adenocarcinoma ( PDAC ). Few studies exist on the distribution and state of nerve fibers in PDAC tissue and their clinicopathological impacts. The aim of the present study was to investigate the clinicopathological characteristics and prognostic value of intrapancreatic neural alterations in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 32 publications
6
49
0
Order By: Relevance
“…An increased density of nerve fibers in the tumor lesion is correlated with high-grade disease and increased pathological stage, including for cancers of head and neck [ 68 ], breast [ 69 ], lung [ 70 ], stomach [ 71 ], prostate [ 26 , 62 ], colon and rectum [ 72 ]. For PDAC it is suggested to be the other way around: a low nerve fiber density correlates with a poorer survival [ 73 ]. In another study, a high nerve fiber density of the parasympathetic nerve fibers correlated with tumor budding and a poor survival [ 74 ].…”
Section: Crosstalk Between Neural Systems and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…An increased density of nerve fibers in the tumor lesion is correlated with high-grade disease and increased pathological stage, including for cancers of head and neck [ 68 ], breast [ 69 ], lung [ 70 ], stomach [ 71 ], prostate [ 26 , 62 ], colon and rectum [ 72 ]. For PDAC it is suggested to be the other way around: a low nerve fiber density correlates with a poorer survival [ 73 ]. In another study, a high nerve fiber density of the parasympathetic nerve fibers correlated with tumor budding and a poor survival [ 74 ].…”
Section: Crosstalk Between Neural Systems and Cancermentioning
confidence: 99%
“…Interestingly, lower intrapancreatic neural density in the tumor area was linked to shorter OS with multivariate analysis [ 73 ]. Related research in CCA mainly focused on PNI prevalence and patient survival [ 45 , 99 , 104 ].…”
Section: Pathological Features Of Nerve Fibers In Pdac and Ccamentioning
confidence: 99%
“…Although PNI is almost omnipresent in PDAC patients, a clear consensus in terms of the profound impact of perineural invasion on overall survival, disease free survival, early tumor recurrence is still missing. Numerous studies have reported a correlation between PNI and tumor recurrence and/or patients’ survival [8,9,12,18,19,20,21,22,23,24]; however, few studies failed to show PNI as an independent predictor of tumor recurrence (overall and early) and of patient survival [25,26]. These differences are most likely due not only to the retrospective design of the majority of these studies but also to the high variance in histological evaluation of PNI.…”
Section: Clinical Impact Of Perineural Invasionmentioning
confidence: 99%
“…Postganglionic sympathetic fibers mostly run with blood vessels (561,562). Innervation is increased in PaCa (563, 564), nerve fibers forming a dense network that interacts with tumor cells and supports tumor growth and dissemination (565)(566)(567). In fact, PaCa metastasize by PNI.…”
Section: Neural Invasion In Pancreatic Cancermentioning
confidence: 99%